Penerapan Model Pembelajaran Discovery Learning Dalam Meningkatkan Keterampilan Proses Sains, Berpikir Kritis, dan Percaya Diri Siswa - Christina Lina Yuliati; Nancy Susianna (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
Science process skills, critical thinking, and self-confidence are life skills that take an important role in everyone’s life, so they need to be developed at an early age. All of those competencies were not yet developed well in grade 1F students in the elementary school SD XYZ Tangerang. The aim of the research was to analyze the application of Discovery Learning model in order to improve grade 1F students’ ability in science process skills, critical thinking, and self-confidence. The research method was class action research. The research was applied to 29 students in the grade 1F elementary school SD XYZ Tangerang as the subject of the study. Students’ progress in their science process skill, critical thinking, and self-confidence was measured by a set of rubrics. The results showed a significant improvement in the students from the first, second, and third cycle. The average science process skill score in the first cycle was 54.60, in the second cycle was 79.60, and in the third cycle was 87.64. The average critical thinking score in the first cycle was 63.51, in the second cycle was 77.01, and in the third cycle was 85.63. The average self-confidence score in the first cycle was 59.77, in the second cycle was 76.72, and in the third cycle was 82.18. Based on the result, it was concluded that Discovery Learning model can improve the science process skill, dan self-confidence in the Science Lesson for grade I F students in the elementary school SD XYZ Tangerang.